Infrared thermography and feeding behavior of lambs fed increasing levels of safflower grains - Ferreira, Mateus Silva [UNESP]; Goes, Rafael Henrique de Tonissi e Buschinelli de; Martinez, Antonio Campanha [UNESP]; Gandra, Jefferson Rodrigues; Gonçales, Walter Antonio; Bega, Amanda Maristela [UNESP]; Silva, Luan Sitó da [UNESP]; Paz, Jessica Priscila da [UNESP] (FapUNIFESP (SciELO), 2020)
The objective was to evaluate the feeding behavior, physiological responses, and rumen heat emission of lambs fed with safflower grains. Eighteen lambs were randomly distributed in a completely randomized design. Safflower grain was added to the diets in the proportions of 0.0; 7.5 and 15%. The safflower grain did not change the patterns of eating, leisure, or rumination; however, it improved the efficiency of NDF ingestion, by 26%. The head temperature decreased by 1.5 ° C to include 7.5% safflower; and the rectal temperature decreased quadratically with the addition of safflower (39.5 and. 39.08 ° C). There was a linear trend of decreasing head temperature as the inclusion of safflower increased. The temperature of the eyeball decreased by 1.1 ° C when 7.5% of safflower DM was added to the diet and increased by 0.6 ° C when a 15% safflower was added. The ruminal temperature increased linearly for the addition of safflower (1.8 ° C). Safflower
Termografia infravermelha e comportamento alimentar de ovinos alimentados com níveis crescentes de grãos de cártamo